Challenges in Early Learning and Child Care for Quebec's English-speaking Community - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Early childhood education and care (ECEC). Early learning and child care. Nursery school. Preschool. Daycare. Centres de la petite enfance (CPE). There are many names and acronyms, but they all refer to the care and, ideally, educative care of young children in the years before compulsory elementary schooling. Modern wisdom views such programs as essential, and yet, in Quebec, English-speaking families face unique challenges in accessing them. This research brief explores these barriers, current efforts being made to address them, and potential solutions.

Défis en matière d'apprentissage et garde des jeunes enfants au sein de la communauté d'expression anglaise du Québec - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Services de garde éducatifs à l’enfance (SGEE). Éducation à la petite enfance. Maternelle. Préscolaire. Garderies. Centres de la petite enfance (CPE). Les désignations sont nombreuses, mais elles se rapportent toutes à des programmes de garde, et idéalement d’éducation, destinés aux tout-petits avant leur fréquentation obligatoire de l’école primaire. Bien que ces programmes soient aujourd’hui considérés comme essentiels, les familles anglophones du Québec se heurtent à de réels défis pour y accéder. Le présent résumé de recherche se penche sur les obstacles qu’elles rencontrent et les mesures prises ou à prendre pour éliminer ces obstacles.

English Eligibility Certificates : Information about How to Apply for a Certificate and Who Is Eligible to Attend English Schools in Québec - Regional Development Network (RDN) (2023)

Appelate Court Hears Challenges to Bill 21 - Quebec Community Groups Network (QCGN) (2022)

What the Community School Approach Brings to Quebec's English School Sector: Connections, Connections, Connections - Horrocks, Debbie; Loomer, Benjamin; Lamarre, Patricia (Lunch & Learn, 2022)

Educational Vitality of the English-speaking Communities of Quebec : From Bill 101 to Bill 96 and Some Ideological Clarifications - Bourhis, Richard Y. (Coalition for the Future of English Education, 2022)

Déclaration sur le refus du gouvernement de la Coalition Avenir Québec de céder sur les dispositions concernant les étudiants des cégeps anglophones - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Statement on Coalition Avenir Québec Government’s Refusal to Budge on Provisions for English-speaking CEGEP Students - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Committee Discusses Quality of French Taught to Newcomers and English-speakers - Quebec Community Groups Network (QCGN) (2022)

La Commission discute de la qualité du français enseigné aux nouveaux arrivants et aux anglophones - Quebec Community Groups Network (QCGN) (2022)

Committee Closes Debate on CEGEPS and Turns to Universities - Quebec Community Groups Network (QCGN) (2022)

La Commission clôt le débat sur les cégeps et se penche sur les universités - Quebec Community Groups Network (QCGN) (2022)

Committee Continues Debate on the Future of English-language CEGEPS - Quebec Community Groups Network (QCGN) (2022)

La Commission poursuit ses débats sur l'avenir des CÉGEPS de langue anglais - Quebec Community Groups Network (QCGN) (2022)

Committee Continues Discussions Regarding Restrictions on CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

La commission poursuit ses discussions concernant les restrictions relatives aux admissions dans les CÉGEPS - Quebec Community Groups Network (QCGN) (2022)

Analyse minutieuse des futures restrictions concernant les admissions dans les CÉGEPs de langue anglaise - Quebec Community Groups Network (QCGN) (2022)

Future Restrictions for Admissions to English-language CEGEPs Scruitinized - Quebec Community Groups Network (QCGN) (2022)

Committee Begins Examination of Language Restrictions Governing CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

La commission entreprend l’examen des restrictions linguistiques relatives aux admissions au CEGEP - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Obligations of Professionals to Provide Documentation in French - Quebec Community Groups Network (QCGN) (2022)

La commission examine l’obligation des professionnels de fournir leur documentation en français - Quebec Community Groups Network (QCGN) (2022)

Legault Government Must Backtrack on Dawson Decision: QCGN - Quebec Community Groups Network (QCGN) (2022)

QCGN : le gouvernement Legault doit faire marche arrière concernant sa décision au sujet de Dawson - Quebec Community Groups Network (QCGN) (2022)

QESBA Deplores the Blatant Disregard for the English Education Community Following the Nomination of a New Assistant Deputy Minister - Quebec English School Boards Association (QESBA) (2022)

Resolution 2022-01 : Objection to the Definition of “Historic” Anglophones and the Consequent Restrictions to Eligibility for Services in English - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-08 : Quebec English CEGEP Admissions Policy - Quebec Federation of Home and School Associations (QFHSA) (2022)

Rapport sur le Forum sur l'éducation et la vitalité - Macris, Antonia; O'Donnell, Lorraine; Shoumarova, Lina; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Du 3 au 5 novembre 2021, des chercheurs, des praticiens, des intervenants communautaires et des décideurs des quatre coins du Québec se sont réunis virtuellement à l’occasion d’un évènement de trois jours intitulé Forum sur l’éducation et la vitalité : Soutenir l’éducation des minorités de langue anglaise au Québec. Il s’agissait du deuxième forum organisé par la Table d’éducation interordres (ILET), un comité du Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN) de l’Université Concordia, et il avait pour objectif d’encourager la mobilisation en vue d’élaborer au Québec une offre d’enseignement en langue anglaise qui soit saine et viable et favorise la persévérance scolaire, l’accès à de bons emplois dans la province et un fort sentiment d’identité et d’appartenance. Le présent rapport donne une vue d’ensemble du Forum et des principaux messages à retenir.
Keywords: Official Language Minority Community (OLMC)

Report on the Education and Vitality Forum - Macris, Antonia; O'Donnell, Lorraine; Shoumarova, Lina; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
From November 3 to 5, 2021, researchers, practitioners, community stakeholders, and policy makers from across Quebec gathered virtually for a three-day event entitled Education and Vitality Forum: Supporting English-Language Minority Education in Quebec. This was the second forum convened by the Inter-Level Educational Table (ILET), a committee of the Quebec English-Speaking Communities Research Network (QUESCREN) at Concordia University. Its objective was to encourage mobilization around the development of a healthy and sustainable English-language educational offer in Quebec that supports student retention, access to good jobs in the province, and a strong sense of identity and belonging. This report provides an overview of the Forum and key takeaway messages from it
Keywords: Official Language Minority Community (OLMC)

Quebec Online Alliance (QOA) - the Online Campus for Students with Medical Exemptions from the English School Boards Across Quebec Officially Opened this Week - Leading English Education and Resource Network (LEARN) (2021)

Brief Presented to The House of Common Standing Senate Committee on Official Languages Submitted by the Quebec English School Boards Association - Quebec English School Boards Association (2021)
The Quebec English School Boards Association was founded in 1929. The role of the association is to represent the nine English school boards of Québec as well as the Littoral School Board, a special status school board. Our member boards cover the full geographic territory of Québec with some board territories covering more than 400,000 square kilometres, equal to the land area of Spain. Our board student enrolments range from 1,300 (Eastern Shores in the Gaspé region) to more than 25,000 for each of the 2 boards serving the Island of Montr al. Our network is comprised of about 340 schools and adult centres, some with enrolment well below 100 to as many as 2,000. Our boards serve the youth sector from Kindergarten to Secondary V (grade 11). They also deliver Adult Education and Vocational Training. Some of our boards offer pre-kindergarten programs to 4-year-old children and the Adult and Vocational sectors cater to students 16 years of age and older. All told there are approximately 100,000 students in the minority-language English public school system.

QCGN Statement on Superior Court Ruling on Quebec’s Secularism Law : A Good Day for Minority Education Right - Quebec Community Groups Network (QCGN) (2021)

Baisse des effectifs dans le secteur scolaire anglophone du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
La Charte de la langue française (1977)1, également connue sous le nom de Loi 101, a eu un impact fort et durable sur les écoles publiques de langue anglaise2. En vertu de cette loi, les élèves de la maternelle au secondaire dont les parents ou les frères et sœurs canadiens ont été instruits au Canada en anglais ont droit à une éducation publique en anglais. À quelques exceptions près, tous les autres élèves doivent fréquenter des écoles de langue française. Ces clauses éducatives limitent l’accès aux écoles de langue anglaise3 en orientant les enfants d’immigrants nouvellement arrivés vers les écoles publiques de langue française4, ainsi que l’accès des Québécois francophones qui n’ont pas des membres de leurs familles qui ont fréquenté des écoles de langue anglaise.
Keywords: Official Language Minority Community (OLMC)

Challenges Around Resources and Services in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
English-language schools in Quebec struggle with diverse challenges, from urban and rural poverty to being located in isolated and remote areas. These issues impact the services and resources available to students and schools already constrained by a declining student population (Advisory Board on English Education [ABEE], 2018).
Keywords: Official Language Minority Community (OLMC)

Decline of Enrolment in Quebec's English-language School Sector - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The Charter of the French language (1977),1 also known as Bill 101, has had a strong and lasting impact on the English-language public school sector.2 Under this law, kindergarten to secondary school students whose Canadian parents or siblings were educated in Canada in English are entitled to English-language public education. Aside from a few exceptions, all other students must attend French-language schools. These educational clauses limit access to English-language schools3 by routing the children of newly arrived immigrants to French-language public schools,4 as well as restricting the access of Francophone Quebecers with no family history of attending English-language schools.
Keywords: Official Language Minority Community (OLMC)

Les enjeux en matière de ressources et de services dans les écoles de langue anglaise du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Ces enjeux ont un impact sur les services et les ressources disponibles pour les élèves et les écoles, déjà fragilisés par un effectif scolaire en constante diminution (Commission de l’éducation en langue anglaise [CELA], 2018).
Keywords: Official Language Minority Community (OLMC)

Prestation de services aux élèves ayant des besoins particuliers dans les écoles publiques anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Au Québec, un nombre croissant d’élèves sont identifiés comme ayant des besoins particuliers et on estime actuellement que cette population représente un élève sur cinq (20,4 %) dans le système scolaire public (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Keywords: Official Language Minority Community (OLMC)

Provision of Services to Special Needs Students in Quebec's English-language Public Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
In Quebec, a growing number of students are identified as having special needs, and it is currently estimated that this population represents one in five students (20.4%) in the public school system (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Keywords: Official Language Minority Community (OLMC)

Postsecondary Education in the Minority Language : An Overview and Analysis of the Issues - Mariève, Forest; Deschênes-Thériault, Guillaume (Sociopol, 2021)
The advocacy efforts of Francophone minority communities (FMCs) that followed the adoption of the Official Languages Act (1969) and the Canadian Charter of Rights and Freedoms (1982) led to the development and implementation of the provincial and territorial minority-language elementary and secondary school systems. In Quebec, the implementation of the Englishlanguage elementary and secondary school system did not meet with the same level of resistance as that faced by the French-language school systems in FMCs.

University-based Approaches for Older Adults : Adapting Universities for the 100-year Lifespan - McGill Community For Lifelong Learning (MCLL) (2020)
This study, University-Based Approaches for Older Adults: Adapting Universities for the 100-year Lifespan, uses the McGill Community for Lifelong Learning (MCLL) as a case study to probe issues related to seniors’ learning within university contexts, including demographics, effects of learning on the lives of older adults, mutual benefits and expectations for learners and the university community of which they are members. The intention of this research is to enable the continuous improvement of MCLL and, given national and international demographic shifts, to add new perspectives to the literature on the increasingly vital topic of continuing to learn throughout the lifespan.

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

An Adapted Approach to Supporting English-Speaking Children (0-5) and Families in the Province of Quebec - Community Health and Social Services Network (CHSSN) (2018)
The primary objective of this document is to further encourage and inspire English-speaking communities to collaborate with stakeholders in their regions offering programs and services to children and families. The document may also serve as a useful tool for stakeholders to become more aware of specific needs often faced by Englishspeaking children and their families and learn about some of the adapted approaches and initiatives underway.

Resolution 2018-02 : Wider Access to English Education - Quebec Federation of Home and School Associations (QFHSA) (2018)
Keywords: Official Language Minority Community (OLMC)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

The Decline of the English School System in Quebec - Bourhis, Richard Y.; Foucher, Pierre (Canadian Institute for Research on Linguistic Minorities (CIRLM), 2012)
With the adoption of the Charter of the French Language by the Parti Québécois in 1977, Quebec Anglophones were most concerned about the erosion of their educational institutions resulting not only from the out-migration of Anglophones and Allophones to the rest of Canada (ROC), but also from the Bill 101 law stipulating that international immigrants to Quebec could no longer choose to send their children to English schools (Mallea, 1984). Thus, following Bill 101, Quebec Anglophones could no longer count on immigrants to maintain the demographic base necessary to keep open key English medium schools across the province (McAndrew, 2002). However by 1982, Anglophones, as English mother tongue “rights holders”, could now count on their right to English schooling in Quebec as enshrined in Article 23 of the Canadian Constitution.

Bill 103 : Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec - Bourhis, Richard Y.; Foucher, Pierre (Quebec Community Groups Network (QCGN), 2010)
The first part of this brief deals with the declining vitality of the English speaking communities of Quebec (ESCQ) and the strength of the dominant Québécois francophone majority in the Province. We argue that a key premise of Bill 103 is based on the erroneous notion that the French language and its speakers are threatened in the Province of Quebec. This false premise brings the current government to draft Bill 103 with regulations making it virtually impossible for Allophone and immigrant children to be approved as pupils in the publicly funded English schools of the Province. As the past Education Minister Michele Courchesne stated on June 3rd 2010 “I won’t deny that the objective (of Bill 103) is to have as few as possible (approved)”.

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

Educating Today's Québec Anglophone : Brief Presented to the Minister of Education, Recreation and Sports - Advisory Board on English Education (2010)

Creating Spaces for Young Quebecers : Strategic Orientations for English-speaking Youth in Quebec - Quebec Community Groups Network (QCGN) (2009)
Over the past decades, Francophones in Quebec have taken formal steps to preserve and promote their language and culture. To most English-speaking youth growing up in Quebec today, this makes sense and we agree that steps should be taken to protect Quebec’s uniqueness in North America. However, young English-speakers living in Quebec - from Montreal to the North Shore to the Gaspé - face their own set of unique challenges. In small English-speaking pockets scattered throughout the province, young English-speakers struggle to become bilingual, access services, create strong ties with their communities, participate in Quebec society and define their own identities. The members of the Quebec Community Groups Network (QCGN) Youth Standing Committee have worked together over the last year to ensure that this document represents the perspectives of as many youth as possible from a wide array of regions and backgrounds. We have also worked to ensure that the process has been directed by youth and that the voices we have heard are heard by others as well. This is the first time that a significant percentage of English-speaking youth in Quebec have come together from across many regions to address the barriers young people face. It has been exciting to discuss our Quebec roots, our desire to remain in this province and our willingness to move past the linguistic tensions of previous generations. In consultations across eight regions, followed by a provincial forum, we have generated strategies for moving forward together. This document outlines strategies that youth have recommended to help achieve our collective vision for English-speaking youth in Quebec. We encourage the QCGN to work towards this vision for English-speaking youth in Quebec in collaboration with community partners, all levels of government and Francophone organizations.
Keywords: Official Language Minority Community (OLMC)

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.

Quebec Government is Not Applying its Own English Language School Law - Alliance Quebec (AQ) (2003)

Hundreds of Canadian Children Have No Right to Attend English-language Schools in Quebec - Alliance Quebec (AQ) (2003)

The Supreme Court of Canada Agreed to Hear Three Cases Involving 11 Families Who Sought Alliance Quebec's Support in Getting Access to Quebec's English-language School System for Their 25 Children - Alliance Quebec (AQ) (2003)

Important Public Information Meeting Concerning Bill 104 and Its Impact on the Children's Eligibility Right to Receive English-language Instruction in Public Schools - Alliance Quebec (AQ) (2002)

Alliance Quebec Supports Challenge to Bill 104 - Alliance Quebec (AQ) (2002)

Sophia and Dounia Badri Win Access to English School - Alliance Quebec (AQ) (2002)

Quebec Should End Discrimination in Education - Alliance Quebec (AQ) (2002)

Education Policy - Alliance Quebec (AQ) (2002)
The Education Policy of Alliance Quebec is based on certain fundam ental Guiding Principles. These principles are clearly articulated in certain international human rights obligations *(1) and domestic laws ** (2) to guarantee freedom, dignity and social justice for all in a democratic and free society.

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

AQ President Brent Tyler to Appear Before the Quebec Court of Appeal When the Joined Education Appeals are Heard - Alliance Quebec (AQ) (2001)

AQ President Brent Tyler Urges the Review Committee to Respect the Rule of Law - Alliance Quebec (AQ) (2001)

The East Island Chapter of Alliance Quebec Passes a Resolution Supporting the Parents of Students Attending St Patrick Elementary in their Struggle to Save Quebec's First English School - Alliance Quebec (AQ) (2001)

AQ Holds Press Conference to Announce AQ Initiatives to Ensure That Immigrant Children in French Schools, Who Are Two (2) or More Years Behind Their Peers, are Provided with an Opportunity to Receive A Proper Education - Alliance Quebec (AQ) (2001)

AQ Requests Meeting with Premier Landry - Alliance Quebec (AQ) (2001)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Ike and Ifeoma Okwuobi Win Access to English School Case - Alliance Quebec (AQ) (2001)

AQ Pleased by Superior Court Ruling Which Strikes Down Part of Quebec's Language Law - Alliance Quebec (AQ) (2000)

AQ Calls on the Language Minister to Examine Research on French Immersion in Canada or "Second Language Programs in Other Countries" and Provide English-speaking Children in Quebec with the Same Learning Opportunities as Their English-speaking Counterparts - Alliance Quebec (AQ) (2000)

AQ Congratulates the Quebec Liberal Party Youth Wing for its Recommendation to Start Teaching English as a Second Language in Grade 1 instead of Grade 4 - Alliance Quebec (AQ) (2000)

Forced Transfer of Either the Francesca Cabrini or Emily Carr Schools or Both, Goes Against the Quebec Government's Policy - Alliance Quebec (AQ) (2000)

A Brief on Quebec's English-speaking Youth on the Occasion of the Youth Summit - Alliance Quebec (AQ) (2000)
We, the English-speaking youth of Quebec, come before you today to ask that our distinctive voices be heard. We share many of the concerns, problems and preoccupations of our French-speaking brothers and sisters. But we have anguishes, specific and poignant, which are ours alone, and which you will not hear about from the other participants and observers at the Youth Conference.

"Many Sections of the Charter of the French Language Violate the Constitutional Rights of Quebecers:" AQ President William Johnson - Alliance Quebec (AQ) (1999)

Another Victory for Alliance Quebec in its Efforts to Expand Access Rights to English Schools - Alliance Quebec (AQ) (1999)

Quebec Ministry of Education Should Accept Responsibility for Issues that Fall Within its Mandate - Alliance Quebec (AQ) (1999)

Avonelle Titus : A Victory for the English-speaking Community - Alliance Quebec (AQ) (1999)

How to Celebrate "La Fête Nationale" - Johnson, William (1999)

Alliance Quebec Fund for Avonelle Titus - Alliance Quebec (AQ) (1999)

Statement by Alliance Quebec on the Compas-National Post Poll - Alliance Quebec (AQ) (1999)

A Challenge for English School Boards : Regionalization and Vocational Education - Advisory Board on English Education (1998)

Régionalisation et formation professionnelle : Un défi pour les commissions scolaires anglophones - Advisory Board on English Education (1998)

Facts We Ought to Know About Education Rights of Children - Alliance Quebec (AQ) (1998)
Yes. At last. A clear, concise outline of the child's legal rights to attend English school. This is an ongoing story: we hope to expand those rights to open wider the door to English schools. But, meanwhile, parents are entitled to know the existing state of the law and what their child's chances are. Sam Ephraim has done us all a favour by putting the facts down on paper in a quickly digestible form. May many parents be enlightened, and many many children receive the benefit of English schooling.

Minority Parents Excluded from Linguistic School Proposal : AQ - Alliance Quebec (AQ) (1997)

Alliance Quebec Supports Linguistic School Boards - Alliance Quebec (AQ) (1997)

Éducation en anglais : un droit ou un privilège? - Alliance Quebec (AQ) (1997)
Les Québécois anglophones fréquentent nombre d'institutions d'enseignement qui furent créées par la communauté qui continue à les servir. Il s'agit de plus de 300 écoles primaires et secondaires, plusieurs écoles privées, cinq cégeps et trois universités - McGill University et Concordia University à Montréal, et Bishop's University à Lennoxville. La base de la politique d'Alliance Québec sur l'éducation consiste à reconnaître qu'il est indispensable pour notre avenir et celui de nos enfants au Québec que nous puissions compter sur un réseau solide et permanent d'établissements d'enseignement offrant des services de qualité qui reflètent les besoins et les valeurs de la communauté d'expression anglaise. Cette dernière doit aussi jouer un rôle actif dans le processus décisionnel du ministère de l'Éducation.

La réorganisation des commissions scolaires, Amendement constitutionnel - Alliance Quebec (AQ) (1997)

Creating Linguistic School Boards : It Can Be Done Right ; It Can Be Done Now - Hamelin, Michael J.; Weiner, Gerry; Mell, Trent; Johnstone, Darlene; Rabinovitch, Joe; Fogelbaum, Morrie; Housefather, Anthony; Bayne, Edina; Delgado, Pascual (Alliance Quebec (AQ), 1997)

A Brief to the Kenniff Committee on the Implementation of Linguistic School Boards from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1994)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to reform and to the advancement of the education of the child. Now that the Minister of Education has stated his intention to proceed with the implementation QFHSA wishes to contribute to the ideas and actions necessary to ensure that the transition takes place in a manner that focuses on the best interest of the students.

A Response to the Advisory Board on English Education from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1994)

Mémoire présenté à la Commission sur l'avenir politique et constitutionnel du Québec soumis par la Fédération québécoise des associations foyers-écoles - Quebec Federation of Home and School Associations (QFHSA) (1990)
Le mandat de la Commission sur l'avenir constitutionnel du Québec fixé par le gouvernement du Québec est de sonder les citoyens de la province en vue de présenter des recommandations à l'Assemblée nationale pour définir un nouveau programme constitutionnel. Ont été exclus des différentes options par le Premier ministre Robert Bourassa, le statu quo et l'annexion aux États-Unis. La Fédération québecoise des associations foyers-écoles (FQAFÉ) souhaiterait également voir exclure le modèle dit souveraineté-association "nationale", où les provinces partagent une devise commune et pratiquent le libre-échange mais où le Québec obtient le contrôle politique exclusif de domaines névralgiques où les pouvoirs sont actuellement partagés par les gouvernements fédéral et provincial, notamment l'immigration, la main-d'oeuvre, l'éducation, les communications et l'environnement. Ce contrôle s'obtiendrait par un transfert du pouvoir du gouvernement fédéral.

Working Papers on English Language Institutions in Quebec - Schachter, Susan (Alliance Quebec (AQ), 1982)
This project was designed to provide a resource for Quebec's English-speaking community and others who feel the need for information about themselves and those institutions usually identified as "English". The decision that such a resource was needed was based on both objective and subjective criteria. Objectively, the English-speaking population of Quebec is, and always has been, an unstable one; that is, large numbers of English-speaking people have always been among those moving to and from the province, Ieaving behind a relatively small core of their fellows with deep roots in Quebec. This high turn-over in population has affected the continuity of the English-speaking community. Such a state of fluidity has made it difficult to evolve a distinctive English-speaking cultural identity with Quebec as its focal point. On the other hand, it has Ied to a discontinuity in the knowledge of our economic, political and cultural role in Quebec. Hence, the need for a resource such as this.

A Position Paper Regarding 1. the Regulation on the Compulsory [Enrollement] of Pupils and 2. the Draft Regulation on the Knowledge of the Language of Instruction to the Department of Education Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1975)
The submission of this study and its recommendations to the Ministry of Education do not imply the Quebec Federation of Home and School Associations' acceptance and approval of Chapter V (the Language of Instruction, Articles 40 - 44) of Bill 22 nor of the regulations under study.

Brief Concerning Regulation Six - Quebec Federation of Home and School Associations (QFHSA) (1972)
The present submission was pre pared as a result of a two-part Resolution passed at the Annual Meeting of the Quebec Federation of Home & School Associations on May 14th, 1971.

A Submission to the Commission of Enquiry on the Position of the French Language and of Language Rights in the Province of Quebec on Improving French Language Education for Non French-speaking Children - Quebec Federation of Home and School Associations (QFHSA) (1969)
It is our purpose in this brief to show that, while we accept the principle that all people in Quebec should learn to speak French well, there are difficulties which prevent them from doing so. Present teaching methods and the numbers of French-speaking teachers in the English schools are inadequate. Many parents in Quebec are denied the right to choose French schools for their children --- thus the surest path to good French is closed to them. At the same time, there exists among English-speaking people anxiety regarding their linguistic rights in the province. This hampers the expansion of the French language outside the French community.

A Dual Language Educational System for Elementary and Secondary Schools in Quebec : a Brief presented to the Honourable J.J. Bertrand, Premier of Quebec by the Dual Language Education Committee - Quebec Federation of Protestant Home & School Associations (1968)
For the past twenty or more years, the radical changes in educational methods and subject-content, the increasing industrialization and urbanization of society and a new awareness of the importance of education, have made Quebec educators, both French and English, concious of the need for a re-thinking and re-organization of the Quebec educational system. This need found partial expression in the work of the Royal Commission of Inquiry on Education (Parent Commission) and the subsequent creation of the department of Education in 1964.

Presentation to the APPELE Consultation